Analisis Peran Partisipasi Pekerja Perempuan Menikah terhadap Pendapatan Keluarga di Provinsi Bali - Damayanti, Sekar Priyanka; Purwanti, Putu Ayu Pramitha (Peneliti.net, 2025)
The various employment sectors in Bali will definitely require human resources in it. In the workforce there is a labor force participation rate (TPAK) which means the percentage of the total workforce to the population who are ten years old and above. The female labor force participation rate in Bali in 2021 was 67.61 percent and in 2022 was 69.62 percent, which increase of 2.01 percent (Badan Pusat Statistik Bali, 2022). This shows an increase in the contribution of women in the labor sector. This study aims to analyze the effect of work intensity, worker status, education, and age of working married women simultaneously and partially on family income in Bali province. A non-participant observation approach was used by collecting data through the National Labor Force Survey (SAKERNAS) questionnaire organized by the Central Statistics Agency (BPS). The research method applied is multiple linear regression, which involves a series of statistical tests such as normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, F-test, and t-test. The result of this research shows that work intensity, permanent worker status, self-employment status, education, and age of married women in Bali Province simultaneously have significant effects on family income. The result also shows that work intensity, education, and age partially have a significant positive effect on family income, while permanent worker status and self-employment status do not have a significant effect.